Preliminary study of light‐cured hydrogel for endodontic drug delivery vehicle. Issue 1 (22nd July 2014) - Komabayashi, Takashi; Wadajkar, Aniket; Santimano, Sonia; Ahn, Chul; Zhu, Qiang; Opperman, Lynn A.; Bellinger, Larry L.; Yang, Jian; Nguyen, Kytai T.
Abstract: Aim: Direct pulp capping is the treatment of an exposed vital pulp with a dental material to facilitate the formation of reparative dentin and maintenance of vital pulp. A bioengineered drug delivery vehicle has the potential to increase the success rate of pulp capping. The aim of this study was to develop an injectable and light‐curing drug delivery vehicle for endodontic treatment including direct pulp capping. Methods: Polyethylene glycol‐maleate‐citrate (PEGMC) hydrogel was synthesized as a drug delivery vehicle that is composed of PEGMC (45% w/v), acrylic acid (AA) (5% w/v), 2, 2′‐azobis(2‐methylpropionamidine) dihydrochloride (AAPH) (0.1% w/v), and deionized water. The association between prehydrogel‐solution volume and visible light‐curing was examined. The cytotoxicity of the hydrogel was tested using L929 cells in a cell culture system. Ca 2+ release from the hydrogel was determined using calcium hydroxide as the incorporated medicine. Results: The results showed that the light‐curing time for hydrogel is comparable to composite resin. The hydrogel had cell toxicity similar to adhesive systems. Moreover, controlled Ca 2+ release was obtained from the calcium hydroxide incorporated hydrogel. Conclusions: The data suggest that hydrogel should be explored further as a promising drug delivery vehicle for vital pulp therapy and regenerative endodontics.